Changes in Schooling Arrangements and in the Demographic and Social Profile of Teachers in Iceland, 1930–1960 - Garðarsdóttir, Ólöf; Guttormsson, Loftur (Nordic Journal of Educational History, 2014)
This article examines the demographic and social profile of primary school teachers in Iceland over half a century, beginning with the introduction of mandatory elementary school attendance in 1908, with particular focus on changes between 1930 and 1960. During this period, Iceland developed from a rural to a predominantly urban society where most children attended classes in permanent school buildings, in contrast to the ambulatory schools most common at the outset. It is our hypothesis that these rapid social changes affected the composition of the teaching corpus in many ways, particularly as regards gender and class origin. Analysis shows that in the first half of the period, female teachers were more numerous in the capital of Reykjavík, and their social and educational status was higher than teachers outside the capital. Furthermore, female teachers in Reykjavík were less likely to marry and had longer teaching careers than their male colleagues. On the whole, the share of female teachers increased considerably between 1930 and 1960, by which time it had become easier for women to combine teaching with marriage.